2021
DOI: 10.1159/000518436
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Degree of Preference for Extended-Release Naltrexone for Treatment Adherence, Opioid Use, and Relapse

Abstract: <b><i>Background:</i></b> Extended-release naltrexone (XR-NTX) is effective for illicit opioid abstinence as an opioid maintenance treatment. To improve treatment outcomes, patient’s preference for the modality of treatment is an important factor. <b><i>Objectives:</i></b> We aimed to test the relationship between baseline preference for XR-NTX and adherence to treatment, use of illicit opioids, and risk of relapse. <b><i>Methods:</i></b> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These last two variables have also been shown to be associated with reduced drug use and improvements in patients' quality of life (Lynch et al., 2021 ; Zhou et al., 2017 ). For this reason, various addiction treatment programs have among their objectives the promotion of adherence and retention in treatment (Gaulen et al., 2022 ; Reif et al., 2021 ), with both aspects of the therapeutic process regarded as dependent variables in research on this issue (Bedard‐Gilligan, 2018 ; Daigre et al., 2021 ). Thus, given the use of these two variables in the field of addictions, it is unsurprising that retention and therapeutic adherence have been established as outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These last two variables have also been shown to be associated with reduced drug use and improvements in patients' quality of life (Lynch et al., 2021 ; Zhou et al., 2017 ). For this reason, various addiction treatment programs have among their objectives the promotion of adherence and retention in treatment (Gaulen et al., 2022 ; Reif et al., 2021 ), with both aspects of the therapeutic process regarded as dependent variables in research on this issue (Bedard‐Gilligan, 2018 ; Daigre et al., 2021 ). Thus, given the use of these two variables in the field of addictions, it is unsurprising that retention and therapeutic adherence have been established as outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…24,30 Healthcare research is increasingly recognizing that client preferences help predict and explain client behaviour 31,32 and that congruency between clients' preferred treatment and administered treatment optimizes care management and improves treatment outcomes. [33][34][35] Research tools that quantitatively capture robust data while remaining relevant to clients might come at the expense of being complex and cumbersome for both researchers and participants. Developed with input from service users, bestworst scaling (BWS) is a quantitative preference elicitation tool where participants select both the best and worst items from a list of at least three levels across multiple choice sets.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative therapeutic approach to maintain opioid abstinence is complete detoxification and induction to antagonist medication ( [4,5,15]; Kristin Klemmetsby [19,22]). Extended-release Naltrexone (XR-NTX) is an opioid antagonist that blocks the euphoric and sedative effects of opioids and offers pharmacological protection against relapse, re-dependence and overdose [1,2,6]. Several studies have confirmed the clinical efficacy of XR-NTX in reducing the use of illicit opioids and with a non-significant increase in the use of addictive non-opioid substances [8,12,16,20,23].…”
Section: Introductionmentioning
confidence: 99%